A construção de uma abordagem teórico-metodológica para o estudo da argumentação em Educação em Ciências - Ana Paula Souto Silva (2015)
The goal of this research is to evaluate the potential of an alternative methodological approach to the study of argumentation in science classrooms, based on the Pragma-dialectics. We also intend to examine in what ways this approach can integrate elements of Ethnography in Education. To contextualize and to explain this research problem we present a non-exhaustive literature review, which shows the importance of language and argument for teaching and learning processes in science. We also address the need for more descriptive studies, and the use of other theories form the Argumentation Theory field for analyzing argumentative discursive interactions in science classrooms. To build this alternative methodological approach, a deep selection and adaptation of Pragma-dialectical theory was conducted, aiming to integrate Ethnography in Education elements. In this sense, we present contributions of Ethnography in Education and characterized the Pragma-dialectical theory, considering these adaptations. Moreover, as this theory is not widely used in the field of Science Education, we exemplify their potential through characterization and exploratory analysis of empirical data related to two science classrooms: Adult Education and 8th grade. These examples were used as evidence to support a reflection about: i) in what ways this methodological approach allows the characterization of argumentation in different class rooms of science; ii) in what ways this methodological approach enables integration between Pragma-dialectical elements and elements of Ethnography in Education; iii) in what ways this methodological approach enables dialogue with the search field in Science Education. Our results indicate that this alternative methodological approach can contribute with new insights to the characterization of discourse in science classroom. In this sense, this approach makes visible: i) the ways in which people in a science classroom disagree and what aspects of these disagreements are recurring; ii) what people in a science classroom need to know and to provide to participate in disagreement events; iii) what resources are used for solving disagreements and how, throughout the history of the class, resources were being constructed; iv) the diversity of ways to disagree in each class; v) how people learn science by participating disagreements events. Although these results are consistent with several elements of Ethnography in Education, we face some challenges. For instance, the extent to which this methodological approach enables the research to adopt an emic perspective. These results also signaled that this approach may contribute to discussions in the field of Science Education, for example, the definition of argument and reasoning, which establishes dialogue with research on "sense making". In this research, we present some possible discussion of paths that need to be studied in greater depth in future research.